Russia – Mexico: 130 years of relations through the lens of diplomacy and Russian poetry - R. O. Reinhardt (Ибероамериканские тетради, 2020)
The article dedicated to the 130th anniversary of diplomatic relations establishment between Russia and Mexico casts a light upon the key turning points of their evolution within the context of foreign policy, history and culture of both countries. The author focuses on diplomatic contacts and intercultural communication. Alongside Heads of States’ visits and exchange of diplomatic representatives, he elaborates on Russian literature classics, i.e. Konstantin Balmont, Vladimir Mayakovsky and Joseph Brodsky, visiting Mexico. It is implied in the conclusion that ‘proximity’ of the countries’ cultures, similarity and sometimes even synchronicity of respective historical development cycles give grounds for a mutually beneficial interstate dialogue.